2022
DOI: 10.1002/cncr.34156
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of further genotyping H3G34 diffuse hemispheric gliomas

Abstract: Background H3G34‐mutant diffuse hemispheric glioma (DHG) is recognized as a new, distinct entity in the latest World Health Organization classification for central nervous system tumors and is associated with a particularly aggressive course. The authors performed a systematic review and pooled analysis to investigate the frequency of genetic events in these tumors and to determine whether these events were associated with survival trends. Methods Two electronic databases were accessed to search for relevant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 39 publications
0
33
1
Order By: Relevance
“…A study recently published by Vuong et al aimed to highlight the role of genetic events and molecular alterations in prognosis for G34-DHG. 35 Our studies demonstrated different median OS with theirs being slightly lower at 14.4 months compared to 17.3 months in our study. Of note, their study also determined that G34V-mutant tumors had significantly worse OS when compared to G34R-mutant tumors.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A study recently published by Vuong et al aimed to highlight the role of genetic events and molecular alterations in prognosis for G34-DHG. 35 Our studies demonstrated different median OS with theirs being slightly lower at 14.4 months compared to 17.3 months in our study. Of note, their study also determined that G34V-mutant tumors had significantly worse OS when compared to G34R-mutant tumors.…”
Section: Discussioncontrasting
confidence: 67%
“…Also, their study demonstrated the role of EGFR amplification on reducing patient survival, not assessed in our study, and should be further evaluated. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The latest 2021 WHO Classification of Tumors of the Central Nervous System integrated histological features and molecular phenotypes of tumors and further proposed the new tumor classification criteria, which focus on advancing the application of molecular diagnosis in the classification of CNS tumors [2]. In recent decades, molecular markers, including the isocratic dehydrogenase (IDH) mutation, the codeletion of chromosome arms 1p and 19q (1P/19q codeletion), and the H3 G34 mutant, have been demonstrated that play a significant role in the classification, grading, prognosis and treatment of gliomas [3][4][5]. However, these markers have limited sensitivity and accuracy [6].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of DHG, H3 G34m is better than that of glioblastoma, with a median progression-free survival of 9 months and a median overall survival of 18-22 months [1 , 3 , 12] . The relatively favorable prognosis has been attributed to a high frequency (74%-79.5%) of MGMT methylation associated with the sensitivity to alkylating agents in patients with DHG, H3 G34m [3 , 17] . Although MGMT methylation could not be assessed for this case, the patient showed good therapeutic response and continued progression-free survival for 20 months after starting treatments including bevacizumab.…”
Section: Discussionmentioning
confidence: 99%